LITERATURE REVIEW: NEUROLOGICAL ASPECT OF CORONAVIRUS DISEASE 2019 (COVID-19): PART I. OVERVIEW AND PATHOMECHANISM - Arthur H.P Mawuntu; Devina C Mastari; Albertus T Lapian; Agnes K.S Hermawan; Mieke A.H.N Kembuan (Neurologi Manado, 2021)
Since coronavirus disease 2019 (COVID-19) was first reported in China in December 2019, this diseasehas caused a world health crisis and has attracted enormous research interest. The emergence ofneurological manifestations has prompted efforts to understand the COVID-19 pathomechanismsassociated with the nervous system through various studies. This paper discusses the neurological aspectsrelated to COVID-19 infection and neuroinvasion including the underlying mechanisms. Other issuesdiscussed in other parts were clinical manifestations especially associated with neurological aspect, druginteractions as well as disease effects in neurology patients. Understanding this may help manage thepatient.